Library classifications criticisms: Universality, poststructuralism and ethics - Martínez Avila, Daniel; Guimarães, José Augusto Chaves [UNESP] (My University, 2013)
We study library classifications criticisms from a poststructuralist and pragmatist point of view that rejects the idea of universality in knowledge organization systems. From this perspective, we analize the seminal texts on library classifications criticisms and conclude that the seek of neutrality in some of these texts is not only an impossible goal but also a contradiction in the representation of different cultures. Therefore, we suggest the commitment with the goals and the recognition of bias in library classifications as an important device for achieving a transcultural ethics in knowledge organization and representation.
Keywords: Bias; Ethics; Knowledge organization and representation; Library classifications; Poststructuralism; Pragmatism; Universality